Studies on the design, synthesis and stability of novel anti-allergy agents - Finn, Deirdre Frances (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2012)
The purpose of this project was to design and synthesise novel classes of anti-allergy compounds using 1-tetralone as the principal building block. This thesis is introduced with an overview of the prominent role played by mast cells and their chemical mediators in the onset and maintenance of an allergic reaction. The importance of the antibody, immunolglobulin E (IgE) binding to its high affinity receptor, FCERI expressed on the surface of mast cells to trigger the allergic signalling cascade is outlined. The release of the mediators from mast cells; both preformed and newly synthesised are discussed which leads onto a description of some of the allergic diseases associated with activated mast cells. There then follows a detailed report on therapeutic agents that are used as anti-allergy agents. This discussion on antiallergic agents encompasses those that are clinically prescribed, isolated from natural sources, biological and newly synthesised. Chapter 1 closes with a description of the novel mast cell stabilising compounds developed within this Thesis. Chapter 2 sets out to overcome some of the concerns associated with potent mast cells stabilisers that were previously synthesised by other members of the group. The aims of this Chapter were firstly, to synthesis an analogous series of tetralol-based compounds which contained a reduced number of asymmetric centres and secondly, to enhance the solubility profile of this series by incorporating a range of water-solubilising groups into their structures via an ester link. Several compounds from both series displayed excellent activity in vitro of which, (2.18) and (2.20) were the most promising candidates. However, their level of activity was not translated in an in vivo model of passive cutaneous anaphylaxis, although (2.20) did offer partial inhibition of passive cutaneous analphylaxis in vivo.
Keywords: Pharmacy, Ph.D.; Ph.D. Trinity College Dublin